PENGGUNAAN MEDIA PEMBELAJARAN DALAM MEMBANTU MENINGKATKAN PEMAHAMAN SISWA TERHADAP PERSAMAAN LINIER SATU VARIABEL - Jihan Azizah; Yenny Anggreini Sarumaha (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
This study amed at helping students to understand concepts of linear equation with one variable. In this study, researcher used learning media in the form of cards which later on could be used by students to enhance their understanding towards linear equation with one variable and solving problems related to linear equation with one variabel. This study is a descriptive qualitative study involving some high school students from one Junior High School in Yogyakarta. Based on the study that had been connected, can be drawn that the used of learning media could help students understand more the concept of linear equation with one variable. The cards also helped stduents in solving mathematics problems related to linear equation with one variable. Anothe advantages of the media that emerged during the research was students used media as a tool to communicate their ideas to their friends